2007
DOI: 10.1002/qj.141
|View full text |Cite
|
Sign up to set email alerts
|

An observed and analysed stratospheric ozone intrusion over the high Canadian Arctic UTLS region during the summer of 2003

Abstract: An exceptional ozone increase in the upper troposphere-lower stratosphere region has been recorded by an ozone sounding performed over the high Canadian Arctic at the beginning of August 2003. Simultaneously observed low humidity and low tropopause height suggest that this anomalous ozone enhancement is attributed to a downward transport from the stratosphere. This latter transport is investigated by using the Ertel potential vorticity field calculated from the ECMWF analyses. The occurrence of such high ozone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…These parameterizations may avoid the impact of misspecified or poorly-known chemical species. By construction, such schemes have no intrinsic trend and then are useful for simulations of several years (e.g., Hadjinicolaou et al, 2005) and data assimilation (e.g., Semane et al, 2007;Massart et al, 2009).…”
mentioning
confidence: 99%
“…These parameterizations may avoid the impact of misspecified or poorly-known chemical species. By construction, such schemes have no intrinsic trend and then are useful for simulations of several years (e.g., Hadjinicolaou et al, 2005) and data assimilation (e.g., Semane et al, 2007;Massart et al, 2009).…”
mentioning
confidence: 99%
“…Hoskins et al (1985) [4] acknowledged the analysis of isentropic potential vorticity (PV) maps as a crucial diagnostic tool for tropopause folds. For instance, a decrease in tropopause height, which is induced by a cyclonic isentropic PV flow anomaly, displaces stratospheric air into the troposphere and an increase in its height, which is induced by an anticyclonic isentropic PV flow anomaly, displaces tropospheric air into the stratosphere [5]. As a consequence, of this "PV thinking", there has been enormously increased interest in using PV for diagnosing cyclogenesis, for research and operational forecasting purposes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Data assimilation studies that focused on UTLS chemical fields started with Cathala et al (2003), who assimilated subsonic flight-level observations of ozone. Later, Semane et al (2007) assimilated O 3 data from a limb sounder (Michelson Interferometer for Passive Atmospheric Sounding) to diagnose a case study of STE over arctic regions. It has been shown that assimilation of stratospheric ozone data from a limb sounder improves the spatial structure of the ozone fields in the UTLS.…”
Section: Introductionmentioning
confidence: 99%
“…Data assimilation has the capability to overcome possible deficiencies of the MOCAGE model in the UTLS (see, e.g., Semane et al, 2007;Barret et al, 2008;El Amraoui et al, 2010;Barré et al, 2012). The aim of this study is to quantify the impact of the assimilation of O 3 and CO data on the UTLS at extratropical latitudes.…”
Section: Introductionmentioning
confidence: 99%